Improving Digital Library Experiences and Support with Online Research Guides - Brewer, Laura; Rick, Holly; Grondin, Karen A. (Online learning (Newburyport, Mass.), 2017)
With a goal of improving the development and delivery of effective online information literacy resources, the purpose of this study was to look at how program level and the timing of the introduction of a Literature Review library guide influenced online business student perceived value of the resource.  A population of undergraduate business students (N=355) and online MBA students (N=319) were introduced to a Literature Review library guide during specific points in their programs.  Students were asked to complete an online survey that included 17 closed-ended items designed to measure perceived usefulness, satisfaction and likeliness to use the guide again.  The survey also included two open-ended questions asking students to discuss those elements of the guide they found most valuable and whether any features had not been included in the guide, but which they would have liked to see. The data collection strategy required faculty post information about the Literature Review library guide and the survey in their courses at two specified times in the course. A low response rate (3.5%) resulted from inconsistencies in faculty including information about the guide and study in their courses.  Although the small sample size (n=24) limited the planned analysis and resulted in no statistical significance between groups, descriptive findings were reported, and trends were used to revise the resource and inform future development of library research guides. Overall, students reported being satisfied with the resource and found it usable.  Graduate students were more likely to report elements of the guide that supported effective search and evaluation strategies were valuable; whereas, undergraduate students tended to value the links to writing resources.  Student feedback also suggested that the earlier the guide was introduced in the program, the more likely students would use the resource.  Adopting a model that embeds resource guides early, and aligning guide content with the curriculum should lead to increased use of the resource.